Utilizing an Implicit Health Analysis Integrated Simulation for Hospital-Nurse Staffing Strategy - Paul, Abhisan; Biswas, Diganta; Jana, Radha Krishna (International Journal of Computer Sciences and Engineering, 2026)
This summary presents the application of an integrated simulation platform for the analysis of poor health in practical nursing care. The platform uses advanced techniques to model and analyse the complex health behaviours of nursing home residents. The platform leverages implicit health analysis to capture hidden patterns and subtle changes in people's health to better understand their needs. Through simulation-based evaluation, various aspects of the strategy can be analysed, including employee engagement, community health, and the need for assistance. The platform provides the framework for improving employee decisions by identifying the best strategies to meet the diverse and changing needs of nursing home residents. Using this new approach, nursing homes can improve care, reduce labour costs and ultimately improve residents' overall quality of life